VOCAL LEARNING AT THE GANESHA DHEVA MUSIC NON-FORMAL INSTITUTION IN TULUNGAGUNG REGENCY : VOCAL LEARNING AT THE GANESHA DHEVA MUSIC NON-FORMAL INSTITUTION IN TULUNGAGUNG REGENCY - Erika, Erika Dwi Anggreini; Rahayu, Eko Wahyuni (Solah, 2025)
This study discusses the vocal learning process at Ganesha Dheva Music. The purpose of this study is to describe the vocal learning and learning outcomes of Ganesha Dheva Music as a non-formal institution in Tulungagung. The study was conducted using a descriptive qualitative approach. Data were collected through direct field observations, interviews with relevant parties, and activity documentation. Data analysis techniques were carried out using steps such as data collection, data reduction, data presentation, and drawing conclusions. To test the validity of the data, the researcher used triangulation techniques. From the results of the study, it can be concluded that the implementation of learning at Ganesha Dheva Music is based on the curriculum used as a reference by the trainer. In delivering the material, the trainer utilizes lecture, demonstration, and drill methods so that students can understand vocal techniques more effectively. Seven learning components were identified, namely: objectives, materials, students, teaching staff, methods, media, and evaluation. Learning outcomes are achieved through holding an annual concert, which also serves as a forum for assessing student abilities and student achievements in various competitions. This study shows that non-formal music course institutions can be an effective forum for developing vocal abilities and students’ overall character.